Study of blood groups and throat swab culture in chronic tonsillitis among pediatric age group - M. S., Sudhakar Rao; P., Apoorva; K., Keerthi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic tonsillitis is a disease of childhood with a peak incidence at 5-6 years of age and the commonest organism being Group A beta hemolytic streptococcus (GABHS). Accurate diagnosis of streptococcal infection is essential to limit transmission, reduce the complications and period of communicability. To study the association between blood groups and culture findings of throat swab in chronic tonsillitis among pediatric age group is the aim of our study. Methods: 60 pediatric patients of clinically diagnosed chronic tonsillitis of both genders who attended outpatient department of otorhinolaryngology and head and neck surgery VIMS, Ballari, Karnataka, India were included in this study on simple random basis. Throat swabs obtained from them were subjected for culture test along with blood grouping and Rh typing. Results: In our study, among 60 patients, who presented with recurrent episodes of throat pain for duration of <1 year were 31 (51.7%), of 1-3 years were 15 (25%) and of >3 years were 14 (23.3%). 42 patients (70%) had grade 3 tonsillar enlargement, 14 (23.3%) had grade 2 and 4 (6.7%) had grade 4 tonsillar enlargement. 22 were of B positive blood group (36.7%), 19 of O positive (31.7%), 12 of A positive (20%) and 7 patients of AB positive blood group (11.7%). Conclusions: Statistically significant association is found among school going age group of both genders infected by the Streptococcal species (p<0.05). Patients of O positive blood group were infected more followed by B positive blood group.